Labor market outcomes during opposite resource shocks: the 2009 and 2012 earthquakes in Italy - Bernini, A (Springer, 2024)
The 2009 and 2012 earthquakes in Italy occurred in a close-knit region and time horizon but differed substantially on both the initial shock to the stock and the subsequent flow of resources. This paper considers the short run impact on the dynamic response of labor market outcomes. Both earthquakes lowered employment and labor force participation by more than 0.5%. With its negative effect on the resources available, the 2009 shock led to a drop in real wages of 1.3% and a sharp—but short-lived—widening of the wage gap generated by the skill premium. The 2012 earthquake, which led firms to upgrade their technology, increased wages by 2.2% and led to a more balanced—but persistent—widening of the wage gap. The predictions of a model developed in this paper are consistent with these results.